Literature Review of Capital Budgeting Practices with Special Reference to Capital Intensive Industries of India - Jha, Abhishek; Arora, Suneel (Prabandhan: Indian Journal of Management, 2019)
The following literature review dealt with a review of past studies conducted on capital budgeting and its related aspects. Both foreign and Indian studies on capital budgeting were included as part of the study. The review tried to critically analyze each and every aspect of every individual study from methodology to statistical tools being applied and findings. An attempt was made to find the relevant gaps in previous studies. It was identified by the review that non-sophisticated methods of capital budgeting and risk assessment are still being used, and this needs to be studied. Additionally, risk assessment methods were revealed to be not sophisticated, which can become part of a future study. This also included a method to adequately incorporate risk information in the capital budgeting process.